The Role of Treatment Perceptions in Intervention Evaluation: A Review - Sidani, Souraya; Fox, Mary (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2020)
Introduction: With the emphasis on patient-centeredness, the interest in examining people’s perceptions of health interventions has resurged. Mounting evidence suggests that people’s perceptions play an important role in their pursuit and use of interventions in the practice and research contexts. In research, participants’ perceptions of the treatments under evaluation affect their behaviors reflected in enrollment, attrition, and treatment implementation (i.e., engagement and enactment by participants), all of which contribute to outcomes. Objectives: The objectives of this review are to generate a common understanding of treatment perceptions and to increase awareness of their role in intervention evaluation trials. Method: A literature review was conducted of conceptual and empirical articles that examined the contribution of participants’ perceptions of treatment to enrollment, attrition, as well as treatment implementation and outcome achievement in intervention evaluation studies. Results: In this paper, we clarify the conceptualization and operationalization of four types of perceptions: acceptability, preferences, credibility and expectancy. We also describe the way in which these perceptions influence participants’ behaviors (i.e., mechanism of action), and we summarize relevant empirical evidence. Implications and conclusion: Researchers are encouraged to account for participants’ perceptions in making inferences about interventions’ effectiveness or lack thereof.